Ilioinguinal and Iliohypogastric Nerve Blocks in Children - Boldbaatar, Odgerel; Maygmar, Ariuntungalag; Ayurzana, Ganchimeg; Lundeg, Ganbold; Orgoi, Sergelen (Central Asian Journal of Medical Sciences, 2017)
Objectives: To examine ilioinguinal and iliohypogastric (ILIH) nerve block techniques among children. Methods: A total of 120 children, aged 1-16 years, were included in this prospective, randomized, single-blinded study. Children received an ILIH nerve block using the conventional fascial click of double “pop” technique on four different points: (Group I, n=30) ILIH block at the junction of the lateral one-fourth, the medial three-fourth in the line from the anterior superior iliac spine (ASIS) to the umbilicus; (Group II, n=28) approximately 2.5 mm medial to the ASIS; (Group III, n=30) 10 mm medial-superior to the ASIS; and (Group IV, n=30) 10mm medial-inferior to the ASIS. Intraoperative hemodynamic changes, postoperative pain intensity, time of first analgesic requirement, and correlation between BMI and groups were examined. Results: The average pain score 2 hours after operation was lowest in group I (1.04±1.23 [Cl 95%, 0-5.3]) and highest in group IV (2.88±2.47 [Cl 95%, 0-9]), a difference of statistically significance (p=0.0027). In group I only, the pain intensity had a weak, positive correlation with BMI (r=0.49, p=0.006). Conclusion: Group I used the best ILIH block technique.